All the Wrong Places [large type] - Fielding, Joy (Thorndike Press large print basic, 2019)
A husband's death, a difficult divorce, a brutal dumping, dissatisfaction with a boring relationship: for various reasons, four women turn to the app "Mr. Right Now," hoping to right-swipe their way to love and happiness.